Feasibility study of palm oil esters as based fluid in drilling operation - Abdul Razak Ismail 215668; Khor, Siak Foo 186118; Regional Conference for Young Scientist (2001 : Universiti Sains Malaysia, Penang) 477553 (Skudai : Universiti Teknologi Malaysia, 2001)
51